2006
DOI: 10.1120/jacmp.v7i3.2200
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of patient organ doses from CT examinations in Tanzania

Abstract: Although the use of CT in medical diagnosis delivers radiation doses to patients that are higher than those from other radiological procedures, lack of optimized protocols could be an additional source of increased dose in developing countries. The aims of this study are, first, to determine the magnitude of radiation doses received by selected radiosensitive organs of patients undergoing CT examinations and compare them with other studies, and second, to assess how CT scanning protocols in practice affect pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…Ngaile's dose range to the brain was 32.5-84.4mGy which was higher than those obtained in our study which was 15-44.7mGy. [36] Also, Organ dose to the lungs, breast, thyroid and heart in this study among the 7 CT units also showed similar differences in dose value with lungs (p<0.001), breast (p<0.001), thyroid (p=0.008), heart (p<0.001), further proving statistically significant differences in protocol used by each CT unit among the hospitals. The dose range to the lung in this study was 15.3-41.7mGy, with an average dose of 30.63mGy.…”
Section: Discussionsupporting
confidence: 55%
“…Ngaile's dose range to the brain was 32.5-84.4mGy which was higher than those obtained in our study which was 15-44.7mGy. [36] Also, Organ dose to the lungs, breast, thyroid and heart in this study among the 7 CT units also showed similar differences in dose value with lungs (p<0.001), breast (p<0.001), thyroid (p=0.008), heart (p<0.001), further proving statistically significant differences in protocol used by each CT unit among the hospitals. The dose range to the lung in this study was 15.3-41.7mGy, with an average dose of 30.63mGy.…”
Section: Discussionsupporting
confidence: 55%
“…The summary of whole process that involved in this study is shown as a flow chart at As a general in the literature, the CTDI 100 air value for conventional CT scanner is reported to be from 17 to 48 mGy [6] [47]. For this dedicated CT scanner, the CTDI 100 values were in the range of values from conventional CT.…”
Section: Methodsmentioning
confidence: 88%
“…Patient doses from CT procedures are relatively higher than doses from other imaging modalities based on ionizing radiation [3]- [6]. From the data published in 2006, the use of CT has increased at a rate of 8% -15% per year for the last 7 -10 years at United States [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have highlighted issues regarding choice of CT parameters and the influence on the dose to patients, the discussions narrowing down on how to optimize the dose [7][8][9][10], noting that there are many possible combinations of choice to optimize CT parameters. Radiology personnel and other users need to be knowledgeable about the various means in controlling radiation output of CT parameters via used tube potential, tube current, slice thickness, pitch, the detector used and etc.…”
Section: Introductionmentioning
confidence: 99%